Dinamika Hubungan Islam dan Agama Lokal di Indonesia: Pengalaman Towani Tolotang di Sulawesi Selatan - Hasse J (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2016)
This study focuses on the relation between Islam and local religion in Indonesia. The common relation pattern occurred in each encounter between Islam and local religion; is that fulfilled by the compromise and the conflict at the same time. In the case at South Sulawesi, the cultural accommodation of Towani Tolotang was able to perform it on a good situation that brought them to be accepted by the Muslims majority without relinquishing their former believes. In certain condition, despite the underlying differences between the two, both Islam and Towani Tolotang can hardly be socially separated from one another. Although the state admitted six religions only, but practically we found various types of religions others. Their adherents strive doing any efforts to keep their existence and continuity for their future. The result of this study shows that Towani Tolotang in its encounter with Islam emerged some types of conflicts and compromises on its dynamics.